Moderating social support on the influence of work-family conflict on job satisfaction - Juliartini, Ketut; Sintaasih, Desak Ketut (International research journal of management, IT and social sciences, 2022)
Human resources (HR) is one of the main elements that occupy a very strategic position in an organization or company. For this reason, every company must be able to maintain its employees and strive to increase job satisfaction. This study aims to analyze the effect of work-family conflict and social support on job satisfaction. This study also examines the moderating role of social support on the effect of work-family conflict on job satisfaction. This research was conducted at the State Savings Bank (BTN) located in Denpasar City, Bali. The sample in this study were permanent employees of BTN in Denpasar, Bali, totalling 103 people. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that work-family conflict had no significant effect on job satisfaction, while social support had a positive and significant effect on job satisfaction. Social support is a moderating variable of the relationship between work-family conflict and job satisfaction. The type of moderating role of the social support variable is the quasi moderator. Specifically, social support weakens the effect of work-family conflict on job satisfaction.